Abnormal pulmonary function in COVID-19 patients at time of hospital discharge - Mo, Xiaoneng; Jian, Wenhua; Su, Zhuquan; Chen, Mu; Peng, Hui; Peng, Ping; Lei, Chunliang; Chen, Ruchong; Zhong, Nanshan; Li, Shiyue (The European respiratory journal, 2020)
On 11 March 2020, the World Health Organization (WHO) declared coronavirus disease 2019 (COVID-19) as a pandemic. As of 22 April, more than 2.4 million cases have been confirmed worldwide [1]. In light of the widely documented lung injuries related to COVID-19 [2, 3], concerns have been raised regarding the assessment of lung injury for discharged patients. A recent report portrayed that discharged patients with COVID-19 pneumonia still have residual abnormalities in chest computed tomography (CT) scans, with ground-glass opacity as the most common pattern [4]. Persistent impairment of pulmonary function and exercise capacity have been known to last for months or even years [5–8] in the recovered survivors from other coronavirus pneumonia (severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS)). However, until now, there is no report in regard to pulmonary function in discharged COVID-19 survivors. This article aims to describe the characteristics of pulmonary function in these subjects. In discharged survivors with COVID-19, impairment of diffusion capacity is the most common abnormality of lung function, followed by restrictive ventilatory defects, which are both associated with the severity of the disease https://bit.ly/2yUaBaT